1, 2‐Benzisothiazol‐3(2H)‐on [MAK Value Documentation in German language, 2018]. Issue 1 (24th January 2018) - Hartwig, A.; ,
Abstract: The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated 1, 2‐benzisothiazol‐3(2H)‐one [2634‐33‐5 ] considering all toxicological endpoints. Available publications are described in detail. Critical effect of 1, 2‐benzisothiazol‐3(2H)‐one is its strong irritancy seen in the rabbit eye test. Irritation of the respiratory tract after inhalation was not investigated but is to be expected. As there are no inhalation studies available, the derivation of a maximum concentration at the workplace (MAK value) for 1, 2‐benzisothiazol‐3(2H)‐one is still not possible and the substance remains assigned to chapter II b of the List of MAK and BAT values. In three prenatal toxicity studies in rats with gavage application, 1, 2‐benzisothiazol‐3(2H)‐one results in reduced foetal body weights and delayed ossifications at 73 or 90 mg/kg body weight and day. The NOAELs for developmental toxicity are 29, 30, and 55 mg/kg body weight and day. 1, 2‐Benzisothiazol‐3(2H)‐one is a skin sensitizer and therefore remains designated with "Sh". It is not genotoxic and valid carcinogenicity studies are lacking. Skin contact is not expected to contribute significantly to systemic toxicity.